Strategi Penyuluh Agama dalam Meningkatkan Kesadaran Beragama Remaja di Dusun Lombo’na Kabupaten Majene - Bate, Nurdalia; Yudi, Wahyudi (Institut Agama Islam Negeri Parepare, 2022)
This research addresses the main problem with sub-problems, namely, what are the strategies of religious instructors in increasing the religious awareness of teenagers in Lombo'na Hamlet and what factors support and hinder religious instructors in increasing the religious awareness of teenagers in Lombo'na Hamlet, Majene Regency. The aim of the research is to find out the strategies and factors that support and hinder religious instructors in increasing teenagers' religious awareness. This research use desciptive qualitative approach. Data collection techniques are observation, interviews and documentation. The results of the research show that the steps taken by religious instructors in increasing the religious awareness of teenagers in Lombo'na Hamlet, Majene Regency, are building relationships with the community which aims to establish good communication in order to create a conducive situation, so that religious instructors can carry out their duties in inviting, calling and being able to convince teenagers to embody religious behavior and carry out a coaching process for target groups, is the right step and must be developed, to turn teenagers into Islamic teenagers. Supporting and inhibiting factors for religious instructors in increasing the religious awareness of teenagers in Lombo'na Hamlet, Majene Regency.